Mechanical and Morphological Properties of Polypropylene/Epoxidized Natural Rubber Blends at Various Mixing Ratio - Mohamad, Noraiham; Zainol, Nur Sharafina; Rahim, Faisal Faris; Ab Maulod, Hairul Effendy; Abd Rahim, Toibah; Shamsuri, Siti Rahmah; Mohd Abid, Mohd Asyadi Azam; Abdollah, Mohd Fadzli bin; Abd Manaf, Mohd Edeerozey (Elsevier, 2013)
This research is to investigate the effect of mixing ratio on the properties of polypropylene (PP) incorporated with epoxidized natural rubber (ENR). The blends of PP/ENR were prepared by melt compounding using an internal mixer and vulcanized through sulfur curing. Mechanical testing such as tensile test, hardness test and impact test were performed to characterize the properties of PP/ENR blends. It was clearly observed that the increase of the ENR percentage increases the toughness and flexibility of the PP/ENR blends. In comparison to the pure PP, the 40/60 PP/ENR blend showed an improvement of elongation at break and impact strength, up to 68% and 56%, respectively. In contrary, the tensile strength and hardness decreases as the amount of PP decreases. The changes were associated to the properties imparted by the elastic chains of cross-linked ENR. The obtained properties showed good correlation with fracture surfaces observed in microscopy analysis performed by Field Emission Scanning Electron Microscope at a magnification of 500 and 5000-x.